Using immunofluorescence techniques to Identify T cells in the foreskin tissue after medical male circumcision - Sebaa, Shorok (Department of Pathology, 2023)
Background: Medical Male Circumcision (MMC) plays an important role in reducing the risk of acquiring sexually transmitted infections (STIs) such as Human papilloma virus (HPV), Herpes simplex type 2 (HSV-2) and HIV-1. The foreskin tissue (FS) is a site abundant in Langerhans cells (LCs), macrophages and T helper cells that express CD4 and CCR5 that are target markers for HIV1 binding and viral infection. The foreskin tissue may also contribute chemokines and cytokines including those that promote inflammation such as IL-17, IL-1β, IL-8, MCP-1 and MIG. The inner foreskin has been shown to contain higher levels of CD4+CCR5+ cells and thus more susceptible to HIV infection compared to the outer foreskin. It was demonstrated that the majority of chemokines measured were highly expressed in the inner foreskin compared to the outer foreskin including CCL27 which was approximately 7-fold higher in the inner foreskin compared to the outer foreskin, in congruent with the higher density of CD4+CCR5+ observed in the epithelium of the inner foreskin. In this study, we hypothesized that CCL27 upregulation in the inner foreskin triggers the recruitment of CD4+ T cells to the epithelium of the foreskin tissue. This could subsequently lead to increased susceptibility to infections in the inner foreskin tissue. The aims of this dissertation were: 1) to measure the impact of CCL27 on the recruitment of CD4+ T cells to the epithelium of the foreskin tissue using immunofluorescence imaging. 2) to compare manual counting and semi-automated method for counting dually positive cells. 3) to use multiparameter flow cytometry to characterize the cells recruited under the influence of CCL27. Methodology: Inner foreskin tissue (n=11) and outer foreskin tissue (n=4) explants were treated with either TNFα or CCL27 and evaluated using immunofluorescence imaging to quantify the levels of CD3 and CD4 expressing cells. Dually positive CD3+CD4+ cells were counted manually using softworx software on the Deltavision microscope and with semi-automated counting using PIPSQUEAK on ImageJ. TNFα and CCL27 treated inner and outer FS cells were immunophenotyped using polychromatic flow cytometry to measure and compare the densities of Th17 and Th22 cells under the influence of the chemokines. Results: Exogenous exposure of inner foreskin tissue explants to TNFα showed a significant increase in the median density of CD3+CD4+ T cells in the epithelium of the inner foreskin (p=0.035) from 78.90 cells/mm2 (IQR: 33.02-127.50) in the unstimulated inner foreskin explants to 134.80 cells/mm2 (IQR: 109.30-206.60). Similarly, the addition of exogenous CCL27 resulted in the median density of CD3+CD4+ T cells in the epithelium of the inner foreskin to increase from the unstimulated inner foreskin (value above) to 164.80 cells/mm2 (IQR: 140.30-184.90, p=0.008). No significant difference was observed in the median density of CD3+CD4+ T cells in the outer foreskin tissue explants after exposure to TNFα and CCL27 (36.50 cells/mm2 , IQR: 18.29-96.65 in the unstimulated tissues compared to 65.12 cells/mm2 , IQR: 7.30-202.80 in the TNFα stimulated tissues; p>0.999 and 24 cells/mm2 , IQR: 11.35-149.40 for the CCL27 stimulated tissues; p=0.686). The median density of CD3+CD4+ T cells in the epithelium of unstimulated inner foreskin tissue showed a trend of an increase from the unstimulated outer foreskin tissue but was not statistically different (127.50 cells/mm2 , IQR: 89.22-219.50 in the inner foreskin compared to 36.52 cells/mm2 , IQR:18.29-96.65 in the outer foreskin explants; p=0.057). When comparing the cell counting methods: manual counting vs semi-automated counting, we observed that the manual counting method estimated higher numbers of dually positive cells compared to the semiautomated method in samples measuring 200 cells/mm2 . Despite these differences, there was strong correlation (R=0.782, p0.999) in CCL27 treated explants. The median frequency of Th22 cells in the inner foreskin in the unstimulated tissue explants was 8.80% (IQR: 1.68-12.60%) vs 5.30% (IQR: 0.96-7.67%, p=0.250) in TNFα treated explants and 4.90% (IQR:0.75-7.39%, P=0.125) in CCL27 treated explants. Meanwhile, the median frequency of Th17 cells in the outer foreskin in the unstimulated tissue explants was 21.60% (IQR: 15.40-37.33%) vs 28.20% (IQR: 14.60-39.40%, P=0.750) in TNFα treated explants and 22.90% (IQR:22.90-29.50%, p>0.999) in CCL27 treated explants. The median frequency of Th22 cells in the outer foreskin in the unstimulated tissues was 4.67% (IQR: 2.30-12.90%) vs 5.37% (IQR: 5.34- 7.58%, P=0.750) in TNFα treated tissues and 4.45% (IQR:3.64-5.98%, p>0.999) in CCL27 treated tissues. Furthermore, FS cells isolated using Dispase had significantly lower median frequencies of cells expressing CCR6 (18.35%, IQR:1.33-28.30%) compared to whole tissue controls (41.90%, IQR: 22.46-67%, p=0.031). This impacted the characterization of CD4+ T cell subsets in FS cells and limited our ability to adequately phenotype and measure the impact of TNFα and CCL27 on FS-derived cells using flow cytometry. Conclusion: This study demonstrates that exogenous exposure of FS to TNFα and CCL27 increased the density of CD3+CD4+ T cells in the epithelium of the inner but not the outer foreskin tissue. It was noteworthy that the density of CD3+CD4+ in the epithelium of the inner foreskin was higher than the outer in the unstimulated tissues, suggesting that the proinflammatory environment in the inner FS potentially leads to higher density of T cells in the inner FS even without exogenous stimulation. These results suggest a possible mechanism for recruiting HIV target cells in the inner foreskin tissue associated with higher levels of CCL27 that recruits HIV-1 target T cells during inflammatory responses. A limitation to this conclusion is the small sample size in the outer foreskin. The study also shows potential bias depending on the method used to quantify dually positive cells, whereby semi-automated counting underestimated the densities of CD3+CD4+ T cells compared to manual counting and therefore careful consideration is required when selecting the quantification method. Furthermore, there were no significant difference in the frequencies of Th17 and Th22 cells after exposure to TNFα and CCL27 using flow cytometry. The effects of Dispase on cell surface marker expression and the low cell yield across the experiments impacted the characterization of Th17 and Th22 using flow cytometry and thus limiting capacity to determine how CCL27 influences these T cell subsets.